Human variability in influx and efflux transporters in relation to uncertainty factors for chemical risk assessment. (June 2020) - Darney, K.; Turco, L.; Buratti, F.M.; Di Consiglio, E.; Vichi, S.; Roudot, A.C.; Béchaux, C.; Testai, E.; Dorne, J.L.C.M.; Lautz, L.S.
Abstract: Transporters are divided into the ABC and SLC super-families, mediating the cellular efflux and influx of various xenobiotic and endogenous substrates. Here, an extensive literature search was performed to identify in vivo probe substrates for P-gp, BCRP and OAT1/3. For other transporters (e.g. OCT, OATP), no in vivo probe substrates could be identified from the available literature. Human kinetic data (Cmax, clearance, AUC) were extracted from 142 publications and Bayesian meta-analyses were performed using a hierarchical model to derive variability distributions and related uncertainty factors (UFs). For P-gp, human variability indicated that the kinetic default UF (3.16) would cover over 97.5% of healthy individuals, when considering the median value, while the upper confidence interval is exceeded. For BCRP and OAT1/3 human variability indicated that the default kinetic UF would not be exceeded while considering the upper confidence interval. Although limited kinetic data on transporter polymorphisms were available, inter-phenotypic variability for probe substrates was reported, which may indicate that the current default kinetic UF may be insufficient to cover such polymorphisms. Overall, it is recommended to investigate human genetic polymorphisms across geographical ancestry since they provide more robust surrogate measures of genetic differences compared to geographical ancestry alone. This analysis is based on pharmaceutical probe substrates which are often eliminated relatively fast from the human body. The transport of environmental contaminants and food-relevant chemicals should be investigated to broaden the chemical space of this analysis and assess the likelihood of potential interactions with transporters at environmental concentrations. Highlights: Extensive literature review of human in vivo transporter probe substrate variability. Hierarchical Bayesian meta-analysis to quantify inter- and intra-ethnic differences. Data for variability in P-gp, BCRP and OATs are mostly limited to healthy adults and covered by the default kinetic UF. Polymorphisms are more robust to study human variability in transporters' kinetics compared to geographical ancestry alone.